Analysis Of Martensitic Transformation And Bending Deformation Of NiTi Arch Wire Against Different Deflection And Temperature Range - Ahmad, Mohd Zuhair (Universiti Sains Malaysia, 2022)
Nitinol (NiTi) arch wires are widely used in orthodontic treatment around the world due to their extreme flexibility and biocompatibility with human body. The arch wire strength of the 4-wing tie bracket assembly is affected by the slip resistance of the patient's teeth when the arch wire and bracket come into contact. In this study, the force applied by the rectangular NiTi arch wire was analyzed as changes in temperature and deflection in the oral cavity. Force-displacement behavior of super elastic arches was investigated using a 3D finite element model. Arch wire microstructure martensite content and phase state were calculated using finite element modelling, dependent on wire deflection range and temperature factors. The numerical model predicted 3-Point bending findings that were in excellent accord with theoretical predictions. The findings may also be compared to other recent studies that have shown a connection to these ones. Force deflection curves were modified by the bond, which changed the martensitic transformation plateau into an inclination as the contact established between the bracket and the wire. Flexing the NiTi arch wire at higher temperatures and deflection released additional loading and unloading forces. At higher temperatures and bigger deflections, an arch wire exposed to greater strain and temperature released more maximum strain during loading than a NiTi arch wire deflected to a lesser degree. As the deflection increases, the martensitic transition of super elastic NiTi arch wires develops. Finally, the martensitic transformation of NiTi sheets was unaffected by temperature fluctuations, according to finite element analysis.